cAMP: fuel for extracellular adenosine formation? - Gödecke, A (Nature Publishing Group, 2008)
It is well known that cAMP, an important intracellular second messenger, is released from many cells upon adenylate cyclase stimulation. Cell surface bound phosphodiesterase together with ecto-5′-nucleotidase may convert the extracellular cAMP to adenosine, which may stimulate in a paracrine and/or autocrine manner cells expressing P1 receptors. In this issue of the British Journal of Pharmacology, Chiavegatti et al. demonstrate the existence of an extracellular cAMP-adenosine cascade in skeletal muscle cells which suggests a link between adrenergic stimulation of contraction, elevated cAMP formation and release and exercise hyperaemia.